The Effect of Employment Status in the UTAUT Model on the Use Behavioral of E-Office Users: Case Study at Politeknik Pariwisata Bali - Putu Ayu Puspitawati; Made Windu Antara Kesiman; Sariyasa Sariyasa (Jurnal Info Sains : Informatika dan Sains, 2023)
Under the auspices of the Ministry of Tourism and Creative Economy, Politeknik Pariwisata Bali as a State University implements E-Government through the implementation of electronic administration in the E-Office application. E-Office facilitates the issuance of assignment letters, the reporting of tasks, the application for leave, and the recording of daily performance through E-Logbook. Despite the fact that E-Office has been adopted since 2020, it is known that user resistance to the system persists. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT) model is employed to characterize the factors that influence the acceptance and utilization of E-Office at the Politeknik Pariwisata Bali. In this analysis, the employment status variable was added to the UTAUT model. It is anticipated that the uniqueness of employment status contributed to the development of the UTAUT model will be a novel aspect of this research, allowing it to make a significant scientific contribution, particularly to the study of the UTAUT model. The five stages of Structural Equation Modeling (SEM), namely model specification, model identification, model estimation, model testing, and model modification, will be applied to model development. A total of 158 respondents with ASN and PTT employment status at Politeknik Pariwisata Bali have completed the questionnaire to capture data. The results indicate, based on the t-statistic value, that performance expectations (PE), effort expectations (EE), social factors (SI), and facility conditions (FC) have a significant impact on system utilization behavior (UB). While employment status has a positive but insignificant effect on user desire (BI), this effect is insignificant.